قيم العمل لدى الطالب الجامعي المقبل على التخرج - هاجر بحطيطة; مريجة عباس (My University, 2018)
Research Title: Values of work for the next university student to graduate research goals Ensure that there are statistically significant differences in the values of work due to the age variable (from 18 to 20), (from 21 to 30), (from 31 to 45), in the sample of the study Ensuring that there are statistically significant differences in the values of work due to the gender variable (female male) in the sample of the study Ensuring that there are statistically significant differences in the work values due to the variable functional status (non-working factor) among the sample members of the study Ensure that there are statistically significant differences in labor values due to the variable of marital status (married, not married) among the sample members of the study Ensuring that there are statistically significant differences in the work values due to the variable of the results of academic achievement (high, medium, low) among the sample of the study The research sample A sample of the students of Ammar Thaliji University studying in the following disciplines (literature, rights, psychology, biology, engineering), from the levels of (bachelor and master For the academic year (2017 2018) and the number of (100) studentsValues are student behavior within the organization in which they work. Work is the job, profession, and physical effort that a person does to achieve a goal that benefits him. A university student is the person who moved from a strict secondary level to university. The most important results: There are no significant differences between the grades of the sample in the level of work values according to specialization (1.2.3.4.5), and from it can not accept the hypothesis of our research and click and accept the zero hypothesis that provides that there are no significant differences in the values of work attributed to the variable specialization. - There are no statistically significant differences in work values according to family status. - There are no statistically significant differences in labor values due to age variable. - There are no statistically significant differences in work values by level of study. - There are no statistically significant differences in the values of work according to the desire to work. Recommendations: - Focusing on the role of unintended education and hidden curricula in disseminating values and disseminating them among students in indirect ways. - Include the values of work in university curricula, and student activities so that the university students directly and spontaneously, become a distinctive approach to their behavior. - Holding conferences and lectures by the teaching staff, which is concerned with how to develop and instill values of work among students. - The need for faculty members to pay attention to the values of work extended from an Islamic source.